Dynamical Coupling Between the Low‐Latitude Lower Thermosphere and Ionosphere via the Nonmigrating Diurnal Tide as Revealed by Concurrent Satellite Observations and Numerical Modeling. Issue 14 (22nd July 2021) - Gasperini, Federico; Azeem, Irfan; Crowley, Geoff; Perdue, Michael; Depew, Matthew; Immel, Thomas; Stromberg, Erik; Fish, Chad; Frazier, Crystal; Reynolds, Adam; Swenson, Anthony; Tash, Ted; et al.
Abstract: The diurnal eastward‐propagating tide with zonal wavenumber 3 (DE3) is an important tidal component due to its ability to effectively couple the ionosphere‐thermosphere with the tropical troposphere. In this work, we present the first results of a prominent zonal wavenumber‐4 (WN4) structure in the low‐latitude ionosphere observed by the Scintillation Observations and Response of The Ionosphere to Electrodynamics (SORTIE) CubeSat mission during May 27–June 5, 2020. Least squares analyses of concurrent in situ ion number density measurements from the SORTIE and the Ionospheric Connection Explorer satellites near 420 and 590 km show this pronounced WN4 to be driven by DE3. Thermosphere Ionosphere Mesosphere Energetics Dynamics Sounding of the Atmosphere using Broad band Emission Radiometry temperatures and Specified‐Dynamics Whole Atmosphere Community Climate Model with thermosphere and ionosphere eXtension output demonstrate that the ionospheric WN4 structure is driven by DE3 propagating from the lower thermosphere. Plain Language Summary: The extent to which terrestrial weather (below ∼30 km) can influence the ionosphere and thermosphere (IT) is a fascinating discovery of the last two decades or so. The IT is known to vary significantly from day to day, and this day‐to‐day weather is largely driven by processes originating in the lower atmosphere, especially during periods of quiet solar activity. Accurate forecasting of the IT variability thus depends on the ability to forecast the component that originates in the lower atmosphere. Ionospheric variability translates to uncertainty in navigation and communications systems, while thermospheric variability translates to uncertainty in orbital and reentry predictions. In this work, we present the first results from the Scintillation Observations and Response of The Ionosphere to Electrodynamics (SORTIE) CubeSat showing a large amplitude structure with four longitudinal peaks in the ionosphere associated with the well‐known diurnal eastward‐propagating tide with zonal wavenumber 3 originating in the tropical troposphere. Our analyses presented in this paper use concurrent SORTIE, Ionospheric Connection Explorer (ICON), and Thermosphere Ionosphere Mesosphere Energetics Dynamics satellite observations during May 27–June 5, 2020 and a whole atmosphere model to interpret SORTIE measurements. Our results suggest SORTIE and ICON to be excellent and complementary observational platforms for studying the influence of terrestrial weather on IT variability. Key Points: First results from the Scintillation Observations and Response of The Ionosphere to Electrodynamics (SORTIE) CubeSat show a large low‐latitude ionospheric wavenumber‐4 (WN4) structure observed concurrently by Ionospheric Connection Explorer (ICON) and Sounding of the Atmosphere using Broad band Emission Radiometry Spectral analyses of SORTIE Ion Velocity Meter (IVM), ICON IVM, and model output demonstrate that the diurnal eastward‐propagating tide with zonal wavenumber 3 tide is responsible for this strong ionosphere‐thermosphere (IT) WN4 coupling SORTIE and ICON IVM provide insights into tropical tropospheric influences on the IT by measuring poorly sampled altitudes simultaneously